The Origin of P-selectin as a Circulating Plasma Protein - Fijnheer, R; Frijns, C J M; Korteweg, J; Rommes, H; Peters, J H; Sixma, J J; Nieuwenhuis, H K (Thrombosis and Haemostasis, 1997)
P-selectin is a 140 kD protein found in the α-granules of platelets and the Weibel-Palade bodies of endothelial cells. On cell activation it is expressed on the cell surface and also secreted into plasma. Whether the circulating soluble P-selectin (sP-selectin) originates from platelets, endothelial cells, or both, is not known. We studied the level of sP-selectin in diseases with different platelet counts, with or without evidence of endothelial cell activation. Endothelial cell activation was confirmed by the detection of sE-selectin and EDl-fibronectin. A significant positive correlation between platelet count and sP-selectin concentration was observed in healthy controls, and in patients with thrombocytopenia due to bone marrow aplasia, or with thrombocytosis (r = 0.85; n = 47; p <0.001). In patients with idiopathic thrombocytopenic purpura (ITP) the sP-selectin concentration was 110 ± 39 ng/ml (n = 10), compared to 122 ± 38 ng/ml in healthy controls (n = 26). However, their mean platelet count was lower (58 X 109/1 versus 241 X 109/1 in the control group). Accordingly, the levels of sP-selectin expressed per platelet increased to significantly higher levels (2.0 ± 1.2 versus 0.6 ± 0.2 fg/platelet in the control group-; p <0.0001). This suggests increased platelet turnover in patients with ITP. High levels of sP-selectin were found in patients with sepsis (398 ± 203 ng/ml; n = 15) and with thrombotic thrombocytopenic purpura (TTP; 436 ± 162 ng/ml; n = 12). Compared with patients with ITP, the concentration of sP-selectin per platelet was higher in patients with sepsis (4.8 ± 4.3 fg/platelet; p <0.005) or TTP (17.1 ± 9.5 fg/platelet; p <0.001). Endothelial cells are very likely to be the source in these patients and the presence of endothelial cell activation was confirmed by increased levels of circulating E-selectin and ED 1 -fibronectin.This study suggests that platelets are the major source of circulating sP-selectin in healthy individuals. Endothelial cell activation is associated with an increased sP-selectin concentration per platelet.